Blog: Menuju Virtual Public Sphere? - Muzayin Nazaruddin (Program Studi Ilmu Komunikasi, 2009)
This article discuss the phenomenon of blog, especially in Indonesian context, through Habermas' perspective. The perspective is theory of public sphere. This article explains from the emergence of blog as a new technology, the development of new perspective in journalism, to examine the existence of blog as public sphere in society.